REMOTE WORKS AS AN INNOVATIVE EMPLOYMENT PRACTICE: IMPLICATIONS FOR JOB SATISFACTION, SOCIAL ISOLATION, AND WORK-FAMILY CONFLICT - Zurab Mushkudiani; Eka Maghlaperidze; Nino Zurashvili; Sophiko Mikabadze (International Journal of Innovative Technologies in Social Science, 2026)
Remote work has become a central topic in organizational research and practice due to its rapid growth and the variety of telecommuting arrangements. This paper aims to synthesize theoretical frameworks and empirical findings related to remote work. The research highlights the conceptual definitions of remote work, its main types, advantages, and disadvantages. Stakeholders can use this paper to understand how remote work relates to job satisfaction. The study also shows the connection between remote work and family life. Remote work is convenient for several reasons, including its flexibility and the interest of talented individuals in remote work opportunities. This type of work environment can also help save taxes for both organizations and employees. However, there are challenges as well. Excessive remote work can lead to professional isolation, a situation where employees lack sufficient communication with their peers. Many workers view remote work as a “dream job,” but in reality, it has its downsides. Employees working exclusively remotely may find it difficult to establish personal relationships with colleagues. This research distinguishes between full-time, occasional, formal, informal, employee-initiated, and employer-initiated contracts. Remote work is associated with increased autonomy, a high level of flexibility, and other valuable tools. Finally, we can conclude that remote work is multidimensional and influenced by many factors. It has both positive and negative aspects, along with various consequences. There are strategies to establish effective remote work for both employees and employers effective.